Neuronal and glial characterization in the rostrocaudal axis of the human anterior olfactory nucleus: Involvement in Parkinson’s disease - Villar-Conde, Sandra; Astillero-Lopez, Veronica; Gonzalez-Rodriguez, Melania; Saiz-Sanchez, Daniel; Ubeda-Banon, Isabel; Flores-Cuadrado, Alicia; Martinez-Marcos, Alino (Frontiers in Neuroanatomy, 2022)
Hyposmia is one of the prodromal symptoms of Parkinson’s disease (PD) and a red flag in clinical diagnosis. Neuropathologically, this sign correlates with α-synuclein involvement in the anterior olfactory nucleus (AON). Neurodegeneration, microgliosis, and astrogliosis in AON are poorly studied, and bulbar AON is the focus of these studies with contradictory results. Additionally, male sex is a risk marker for developing PD, but sexual dimorphism of neural and glial populations in the AON has rarely been considered. The aim of this study was to analyze the density of NeuN, Iba-1, GFAP, and Lewy bodies (LBs), as well as the relationship of these cell type markers with pathology along the rostrocaudal axis of the AON (bulbar, retrobulbar, cortical anterior, and posterior divisions). Cavalieri, optical fractionator, and area fraction fractionator stereological approaches were used for the volume, cell populations and LBs densities, area fraction, and percentage of overlap. Iba-1 and α-syn intensities were measured using ImageJ. In non-PD (NPD) cases, the volume was lower in the AON at the extremes of the rostrocaudal axis than in the intermediate divisions. Cortical anterior AON volume decreased in PD compared with NPD cases. NeuN density decreased rostrocaudally in AON portions in NPD and PD cases. This occurred similarly in Iba-1 but only in PD samples. Iba-1 intensity significantly increased in bulbar AON between PD and NPD. No changes were found in astrocytes. Eight percent of NeuN, 0.1% of Iba-1, and 0.1% of GFAP areas overlapped with LBs area along the AON portions. The data indicate that bulbar AON, which is the most rostral portion in this axis, could play a major role in the pathology. This could be related to the larger area occupied by LBs in these divisions.